Historical Palestinian Conflict, Ottomans, Zionism, and the Religious Formation of Israel (Al-Qamar, 2025)
Palestine has been a land that has been important to three religions: Judaism, Christianity, and Islam. Jews consider it their Holy Land or the Promised Land of “Eretz Israel”, making this land a focal point of Jewish national identity. For both Jews and Christians, this land is the birthplace of Jesus and the birthplace of Judaism and Christianity. For Muslims, the Al-Aqsa Mosque in Jerusalem was the place where the Prophet Muhammad went on his night journey, of Mai’raj. This has attracted many pilgrims, scholars, and monks to this area of the Middle East Many kings and kingdoms have taken control of Palestine throughout history from Canaanites in the late Bronze Age, to Alexander the Great in 330 BCE, to the Romans in 70 CE, to the earliest Muslims in 640 CE, and the Crusaders in the 12th century, to the British for a small time in the 20th century, and to present day Israel. The state of Israel was formed out of a series of fights and conflicts in this land. Palestine is now a centre of many political activities with the most notable and notorious one being the conflict between the states Palestine and Israel. In order to understand Palestinian history regarding how the entire Palestine-Israel conflict started, the starting point should be the Ottoman Empire. The events of the Ottoman Empire had a great role in shaping Palestine as we see today.
Keywords: Palestine; Israel; Romans; Crusaders; Ottomans